Aplikasi Pemrograman Linear Integer Pada Optimasi Keuntungan Produksi Olahan Beras Ketan di Industri Rumah Tangga Desa Long Pejeng - Rosi; Syaripuddin; Desi Febriani Putri (LPPM Politeknik Aceh Selatan, 2025)
Glutinous rice is a variety of rice that plays an important role in local culture, especially in the tradition of opening fields. When the harvest season arrives, local communities usually hold thanksgiving in the form of uman (eating) ubek parties at the beginning of the harvest and post-harvest parties as an expression of gratitude for the harvest. In the tradition of the Dayak community, especially Dayak Kenyah, glutinous rice is used as the main ingredient for making various specialties such as lemang, ubek (kenta), and undat ao. So glutinous rice is used as the main commodity for the household industry in Long Pejeng Village. Various types of processed products produced by this industry, including lemang, fried sticky rice, klepon and bubur candil, use glutinous rice as the main raw material. This study aims to optimize the profit of glutinous rice production by applying integer linear programming. The method used in this research is the simplex method to find the optimal solution, as well as the Gomory Cutting Plane method to obtain a feasible integer solution for each type of product. The results showed that the optimal production quantity was 281 packs per one-time production, consisting of 112 packs of lemang, 56 packs of fried sticky rice, 45 packs of klepon, and 68 packs of candil porridge, with a maximum profit of Rp887,368.00. Optimization using this method is proven to significantly increase profits by 14.4% compared to the previous production method and increase efficiency in the use of raw materials and production capacity